Designing an Educational Game Based on Role Playing Game for The Subject of Algorithms and Programming - Haris, Celine Aloyshima; Jhordy, Ahmed (Journal of Educational Sciences, 2025)
The rapid advancement of technology has significantly affected children’s learning. Consequently, many children become absorbed in online games and feel disengaged or bored with study. Moreover, monotonous teaching methods further contribute to this disengagement. In response to this need, this research aims to develop an RPG-based educational game designed to boost students’ interest and facilitate their understanding of Algorithm and Programming material. To achieve this, the research employs the MDLC method using a waterfall model. In the testing phase, the main menu and gameplay functionality received a score of X = 1, which was categorized as “Feasible”. Media experts’ assessments scored 93.7% and the material expert assessment scored 93.3% for usability testing, each of which fell into the “Very Suitable” category. The student satisfaction reached 79.9% in the “Satisfied” category. Based on these findings, the RPG-based educational game is considered suitable for use as learning media, thereby increasing students’ motivation to learn. Student responses to the RPG-based educational game were positive, as indicated by questionnaires given to students. On average, students described the RPG-based educational game as interesting, easy to understand, and helpful in grasping Algorithms and Programming concepts.